A Portrait of Peers Within Peer-Mediated Interventions: A Literature Review. (June 2022) - Travers, Hilary E.; Carter, Erik W.
Although the impact of peer-mediated interventions on students with intellectual and developmental disabilities (IDD) has been studied extensively, little attention has focused on the peers without disabilities who are so central to these interventions. We reviewed 98 studies to examine the portrait of more than 3, 000 peers without disabilities who have participated in peer-mediated interventions involving middle and high school students with IDD. Peer and student demographics were very diverse, as were the methods for peer recruitment and selection, the interventions they delivered, the settings in which they spent time with students with IDD, and the ways in which they were prepared for these roles. However, reporting in these areas was limited across studies. We offer recommendations for strengthening research and practice focused on the contributions of peers within these evidence-based interventions.